Drug interactions and adverse events in elderly heart disease patients (Brazilian Journal of Pharmaceutical Sciences, 2022)
Chronic and multiple diseases are more prevalent in elderly individuals and, epidemiological highlight can be given to cardiovascular conditions requiring multi-drug therapies, which favor the occurrence of drug interactions. This study aims to analyze potential drug interactions and correlate them with adverse events in elderly heart-disease patients in a hospital setting. This is a prospective description of the analysis of medical prescriptions and records of 80 patients, with data collection performed by using validated instruments during a seven-month period. The drug interactions found were indicated by scientifically recognized databases and subsequently treated statistically with adequate software. 1841 potential interactions between drugs were detected, of which 74.1% did not show any therapeutic benefits, with antithrombotic and analgesic drugs accounting for the worst results. Thenumber of potential interactions was proportional to the occurrence of adverse events, classified at 87.3% as moderate to severe. It is concluded from such results that there is a proportionality between the occurrence of potential drug interactions and the detection of adverse events, with therapeutic management being of great importance for safety, quality and affordability of the treatment.